Study of Jatropha Curcas Extract as a Corrosion Inhibitor in Acidic Medium on Mild Steel by Weight Loss and Potentiodynamic Methods - Gupta, Dipak Kumar; Kafle, KM Anita; Das, Anju Kumari; Neupane, Shova; Ghimire, Anita; Yadav, Braham Dev; Chaudhari, Yogesh; Karki, Nabin; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2020)
The corrosion inhibition properties of methanol extract of Jatropha curcas (JC) were investigated for mild steel (MS) in acidic medium using weight loss and potentiodynamic methods. Corrosion inhibition of MS in 1MH2SO4 was studied in the absence and presence of various concentrations of the methanolic extract of Jatropha curcas barks. The results showed an increase in corrosion inhibition with increasing concentration of the extract. The inhibition efficiency of 1000 ppm JC extract from the weight loss and potentiodynamic polarization methods were approximately 92.0% after 24 hours immersion in the acidic solution. Open circuit potential (OCP) and potentiodynamic polarization measurements showed that the JC extract acts as a mixed-type inhibitor.